Endoscopic Needle Knife Sphincterotome—an Alternative for Retrieval of an Entrapped Nasogastric Tube - Kataria, Hanish (Indian J Surg, 2015)
Knowledge of the use of a nasogastric tube (NG) is integral in medical practice as a whole and more so in gastrointestinal diseases because of its wide range of uses. Accidental fixation of the nasogastric tube during surgery is a rare complication. Various methods have been described for retrieval of an entrapped, retained or stapled nasogastric tube. We describe here a novel technique in which an endoscopic needle knife sphincterotome using a side-view endoscope was used successfully to cut the knots and release the entrapped NG tube. Although stress should always be laid on prevention, the flexible endoscopic approach is a small-duration procedure, a minimally invasive, cost-effective technique for the removal of a nasogastric tube that avoids the need of redo surgery and unnecessary exposure to anaesthesia.